1996
DOI: 10.1038/nm1196-1248
|View full text |Cite
|
Sign up to set email alerts
|

Kappa–opioids produce significantly greater analgesia in women than in men

Abstract: Sex differences in human responses to nociceptive stimuli and painful pathological conditions have generally indicated that women report higher pain levels or exhibit less tolerance than men for given stimulus intensities (reviewed in ref. 1 and 2). However, studies have not evaluated sex differences in analgesic responses. We recently reported that the opioid agonist-antagonist pentazocine, which acts predominantly at kappa-receptors, produced significantly better postoperative analgesia in females than in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
188
2
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(208 citation statements)
references
References 27 publications
12
188
2
6
Order By: Relevance
“…Gear et al have reported that postdental surgery pain relief by opioids acting at the -receptor was greater amongst females than amongst males. 6 Miaskowsi and Levine recently reviewed studies for the period from 1966 to 1998 in which a PCA was used to administer opioids for postoperative pain, and found that a slight majority of studies noted larger PCA opioid consumption amongst males as compared to females 1,[7][8][9] in line with our results. The reasons for this gender related difference remain unclear and several mechanisms may be invoked.…”
Section: Discussionsupporting
confidence: 88%
“…Gear et al have reported that postdental surgery pain relief by opioids acting at the -receptor was greater amongst females than amongst males. 6 Miaskowsi and Levine recently reviewed studies for the period from 1966 to 1998 in which a PCA was used to administer opioids for postoperative pain, and found that a slight majority of studies noted larger PCA opioid consumption amongst males as compared to females 1,[7][8][9] in line with our results. The reasons for this gender related difference remain unclear and several mechanisms may be invoked.…”
Section: Discussionsupporting
confidence: 88%
“…42). Gear and colleagues (10)(11)(12)(13), in contrast, have reported that women are more sensitive to the inhibition of molar extraction pain by a number of nonselective -opioid analgesics including pentazocine. We observed a trend in the opposite direction presently: toward greater analgesia in nonredheaded men than women.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences may exist in pain-processing pathways. Recent studies have demonstrated that female patients experience pain relief with agonist opiate analgesics such as pentazocine, whereas male patients do not (27). opiate receptors together with COX-2 mRNA have been identified in the dorsal horn of the spinal cord, and these mechanisms may interact differently in male and female animals (28).…”
Section: Figmentioning
confidence: 99%